Dye-sensitization of self-assembled titania nanotubes prepared by galvanostatic anodization of Ti sputtered on conductive glass - Stergiopoulos, T.; Valota, A.; V. Likodimos; Speliotis, Th.; Niarchos, D.; Skeldon, P.; Thompson, G.E.; P. Falaras (Nanotechnology, 2009)
Self-organized porous TiO2 nanotubes (NTs) were prepared on conductive glass by galvanostatic anodizing of sputtered titanium in an NH 4F /glycerol electrolyte. DC magnetron sputtering at an elevated substrate temperature (500 °C) was used to deposit 650nm thick titanium films. After anodizing, NTs, 830nm long, with an average external diameter of 92nm, were grown; this gave a high conversion rate of oxide from titanium (1.9), with a 220nm thick layer of titanium, which was not oxidized, located at the base of the tubes. The NTs revealed a mainly amorphous structure, which transformed mostly to anatase upon thermal treatment in air at 450 °C. The tubes were sensitized by the N719 complex and the resultant photoelectrodes were incorporated into liquid dye solar cells (DSCs) and further tested under back-side illumination. High values of Voc (714mV) were obtained under 1 sun (AM 1.5), assigned to low dark current magnitude and large recombination resistance and electron lifetime. In addition, typical values of fill factors (of the order of 0.62) were attained, in agreement with the estimated ohmic resistance of the cells in combination with low electron transfer resistance at the platinum/electrolyte interface. The overall moderate power conversion efficiency (of the order of 0.3%) was mainly due to the low short-circuit photocurrents (Jsc = 0.68mAcm-2), which was confirmed further by the corresponding IPCE values (5.2% at 510nm). The magnitude of Jsc was attributed to absorbed light losses due to back-side illumination of the cells, the low dye loading (due to the limited thickness of anodic titania) and the high charge transfer resistance at the TiO2 /conductive substrate due to the presence of barrier layer(s) underneath the tubes. These preliminary results encourage the DSC community to explore further the galvanostatic anodizing of titanium in order to produce highly efficient porous TiO2 NTs directly on conductive glass. Current work is focusing on achieving complete anodizing of the metal substrate and full transparency for the photoelectrode in order to increase and optimize the resultant cell efficiencies. © 2009 IOP Publishing Ltd.